Kinds of well-being: A conceptual framework that provides direction for caring - Kathleen T. Galvin (International Journal of Qualitative Studies on Health & Well-Being, 2011)
This article offers a conceptual framework by which different kinds and levels of well-being can be named, and as such, provides a foundation for a resource-oriented approach in situations of illness and vulnerability (rather than a deficit-oriented approach). Building on a previous paper that articulated the philosophical foundations of an existential theory of well-being (“Dwelling-mobility”), we show here how the theory can be further developed towards practice-relevant concerns. We introduce 18 kinds of well-being that are intertwined and inter-related, and consider how each emphasis can lead to the formulation of resources that have the potential to give rise to well-being as a felt experience. By focusing on a much wider range of well-being possibilities, practitioners may find new directions for care that are not just literal but also at an existential level.